2009
DOI: 10.1159/000218155
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Eccrine Hidrocystomas – from Diagnosis to Treatment: The Role of Dermatoscopy and Botulinum Toxin

Abstract: Background: Eccrine hidrocystomas are rarely described benign cystic lesions, mainly presenting in middle-aged women in the centrofacial area and usually associated with a chronic course, seasonal variability and no proved and consistently efficacious treatments. Case Report: We report 2 patients, a 45- and a 56-year-old woman, with multiple facial eccrine hidrocystomas suggested by dermatoscopy, confirmed by histology and treated with botulinum toxin A with excellent results. Conclusion: Our report stresses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 40 publications
2
27
0
1
Order By: Relevance
“…Eccrine hydrocystomas treated with topical(6) and intralesional (7)(8)(9)(10) botulinum toxin have been reported to have good results. Given that syringomas have a similar origin as eccrine hidrocystomas and that BTXA inhibits secretion of sweat gland, we decided to use BTXA to treat periorbital syringomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eccrine hydrocystomas treated with topical(6) and intralesional (7)(8)(9)(10) botulinum toxin have been reported to have good results. Given that syringomas have a similar origin as eccrine hidrocystomas and that BTXA inhibits secretion of sweat gland, we decided to use BTXA to treat periorbital syringomas.…”
Section: Discussionmentioning
confidence: 99%
“…(4)(5)(6) In the literature, several case reports have revealed that multiple eccrine hydrocystomas treated with intralesional and topical botulinum toxin had good results. (6)(7)(8)(9)(10)(11) Since syringomas have similar origin as eccrine hidrocystomas and that BTXA inhibits function of sweat glands, the application of BTXA might have some beneficial effects for patients with syringomas. In the current study, we retrospectively evaluated the efficacy of CO2 laser combined with BTXA for treating syringomas and compared its safety and efficacy to CO2 laser only.…”
Section: Introductionmentioning
confidence: 99%
“…Successful treatment of eccrine hidrocystomas with botulinum toxin A has also been described recently. [8] Laser (585-nm flash lamppumped pulse dye laser) appears to be a viable and efficient form of treatment of EH, as there is a lower risk of scarring than with surgical intervention. [9] Electrocautery with a fine tipped probe may also be effective.…”
Section: Discussionmentioning
confidence: 99%
“…There was excellent response at first session in around 80% of both groups with mean duration of 7 months of the drug efficacy (Correia et al, 2009).…”
Section: Multiple Eccrine Hidrocystomasmentioning
confidence: 92%